Phosphodiesterase Inhibitors Suppress Lactobacillus casei Cell-Wall-Induced NF-κB and MAPK Activations and Cell Proliferation through Protein Kinase A—or Exchange Protein Activated by cAMP-Dependent Signal Pathway - Takekatsu Saito; Naotoshi Sugimoto; Kunio Ohta; Tohru Shimizu; Kaori Ohtani; Yuko Nakayama; Taichi Nakamura; Yashiaki Hitomi; Hiroyuki Nakamura; Shoichi Koizumi; Akihiro Yachie (The Scientific World Journal)
Specific strains of Lactobacillus have been found to be beneficial in treating some types of diarrhea and vaginosis. However, a high mortality rate results from underlying immunosuppressive conditions in patients with Lactobacillus casei bacteremia. Cyclic AMP (cAMP) is a small second messenger molecule that mediates signal transduction. The onset and progression of inflammatory responses are sensitive to changes in steady-state cAMP levels. L. casei cell wall extract (LCWE) develops arteritis in mice through Toll-like receptor-2 signaling. The purpose of this study was to investigate whether intracellular cAMP affects LCWE-induced pathological signaling. LCWE was shown to induce phosphorylation of the nuclear factor κB (NF-κB) and mitogen-activated protein kinase (MAPK) signaling pathways and cell proliferation in mice fibroblast cells. Theophylline and phosphodiesterase inhibitor increased intracellular cAMP and inhibited LCWE-induced cell proliferation as well as phosphorylation of NF-κB and MAPK. Protein kinase A inhibitor H89 prevented cAMP-induced MAPK inhibition, but not cAMP-induced NF-κB inhibition. An exchange protein activated by cAMP (Epac) agonist inhibited NF-κB activation but not MAPK activation. These results indicate that an increase in intracellular cAMP prevents LCWE induction of pathological signaling pathways dependent on PKA and Epac signaling.